2022
DOI: 10.13057/biodiv/d230327
|View full text |Cite
|
Sign up to set email alerts
|

First report of seaweed-associated yeast from Indonesia: Species composition and screening of their polysaccharides-degrading enzymes

Abstract: Abstract. Sibero MT, Frederick EH, Sabdono A, Wijayanti DP, Pringgenies D, Radjasa OK, Zilda DS, Murwani R. 2022. First report of seaweed-associated yeast from Indonesia: Species composition and screening of their polysaccharides-degrading enzymes. Biodiversitas 23: 1408-1419. Yeast has been widely utilized in various industries due to its enzyme properties. Therefore, plenty of studies focus on exploring yeast biodiversity from diverse sources. However, there are limited reports regarding marine yeast biodive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 80 publications
0
6
0
1
Order By: Relevance
“…Furthermore, Hodhod et al (2020) also informed about the antibacterial activity of crude extract of H. werneckii against Methicillin-resistant Staphylococcus aureus (MRSA), Campylobacter jejuni and Salmonella typhimurium. Interestingly, a marine H. werneckii SUCCY001 was isolated as a seaweed-associated marine yeast (Sibero et al 2022). This study also discovered the ability of H. werneckii SUCCY001 to degrade several marine polysaccharides.…”
Section: Introductionmentioning
confidence: 56%
“…Furthermore, Hodhod et al (2020) also informed about the antibacterial activity of crude extract of H. werneckii against Methicillin-resistant Staphylococcus aureus (MRSA), Campylobacter jejuni and Salmonella typhimurium. Interestingly, a marine H. werneckii SUCCY001 was isolated as a seaweed-associated marine yeast (Sibero et al 2022). This study also discovered the ability of H. werneckii SUCCY001 to degrade several marine polysaccharides.…”
Section: Introductionmentioning
confidence: 56%
“…Plenty of microorganism have been discovered from Panjang Island ecosystem, from prokaryotic like bacteria to eukaryotic microorganisms such as fungi [17][18][19] . Our previous study has succeeded in obtaining various species of association bacteria from this location such as Salinicoccus roseus, Sphingobium yanoikuyae, Streptomyces lateritius, Labrenzia marina, and Halomonas meridiana [20,21].…”
Section: Resultsmentioning
confidence: 99%
“…The selection of A. melanogenum MTGK.31 was based on our previous study which reported its ability in producing extracellular polysaccharides-degrading enzymes (EPEs) (Sibero et al, 2022). This yeast had a large colony size, filamentous shape and margin, convex elevation, smooth texture, and white cream color.…”
Section: Aureobasidium Melanogenum Mtgk31mentioning
confidence: 99%
“…However, most of them mainly focused on the lactic acid bacteria (LAB) and baker yeast Saccharomyces cerevisiae as the fermenting agents, while the utilization of marine yeast is rarely studied (Sharma et al, 2020). Hence, as the preliminary experiment, our previous study has reported the potential of seaweed-associated yeast Aureobasidium melanogenum MTGK.31 as one of the extracellular polysaccharides degrading enzymes (EPEs) producers (Sibero et al, 2022). Considering the outstanding result of microbial fermentation on seaweed biological properties in previous studies, in this work, we aimed to investigate the potential of marine yeast A. melanogenum MTGK.31 as the fermenting agent on Gracilaria verrucosa's biological properties and characterize the seaweed metabolites profile and antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%